2020
DOI: 10.1080/07391102.2020.1763202
|View full text |Cite
|
Sign up to set email alerts
|

Identification of new anti-nCoV drug chemical compounds from Indian spices exploiting SARS-CoV-2 main protease as target

Abstract: The 2019-novel coronavirus (nCoV) has caused a global health crisis by causing coronavirus pandemic in the human population. The unavailability of specific vaccines and anti-viral drug for nCoV, science demands sincere efforts in the field of drug design and discovery for COVID-19. The novel coronavirus main protease (SARS-CoV-2 Mpro) play a crucial role during the disease propagation, and hence SARS-CoV-2 Mpro represents as a drug target for the drug discovery. Herein, we have applied bioinformatics approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
111
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(118 citation statements)
references
References 19 publications
5
111
0
2
Order By: Relevance
“…In recent times many computational studies have been carried out to repurpose various FDA approved antiviral drugs for COVID-19 treatment by targeting SARS CoV-2 Mpro (Arun et al, 2020;Elmezayen et al, 2020;Kandeel & Al-Nazawi, 2020;Mahanta et al, 2020;Muralidharan et al, 2020). Apart from these drugs, various medicinal phytochemicals have been proposed as potent SARS CoV-2 Mpro inhibitors (Aanouz et al, 2020;Bhardwaj, Singh, Sharma, Rajendran, et al, 2020;Das et al, 2020;Enmozhi et al, 2020;Gyebi et al, 2020;Islam et al, 2020;Joshi et al, 2020;Umesh et al, 2020). Even many plant-derived natural polyphenols (Oolonghomobisflavan-A from the tea plant Camellia sinensis L., epigallocatechin gallate, epicatechingallate and gallocatechin-3-gallate from green tea Camellia sinensis) having antiviral properties are effective SARS CoV-2 Mpro inhibitors (Bhardwaj, Singh, Sharma, Rajendran, et al, 2020;Ghosh et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In recent times many computational studies have been carried out to repurpose various FDA approved antiviral drugs for COVID-19 treatment by targeting SARS CoV-2 Mpro (Arun et al, 2020;Elmezayen et al, 2020;Kandeel & Al-Nazawi, 2020;Mahanta et al, 2020;Muralidharan et al, 2020). Apart from these drugs, various medicinal phytochemicals have been proposed as potent SARS CoV-2 Mpro inhibitors (Aanouz et al, 2020;Bhardwaj, Singh, Sharma, Rajendran, et al, 2020;Das et al, 2020;Enmozhi et al, 2020;Gyebi et al, 2020;Islam et al, 2020;Joshi et al, 2020;Umesh et al, 2020). Even many plant-derived natural polyphenols (Oolonghomobisflavan-A from the tea plant Camellia sinensis L., epigallocatechin gallate, epicatechingallate and gallocatechin-3-gallate from green tea Camellia sinensis) having antiviral properties are effective SARS CoV-2 Mpro inhibitors (Bhardwaj, Singh, Sharma, Rajendran, et al, 2020;Ghosh et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…While, structural composition of domain III mainly consists of alpha-helices (Anand et al, 2005;Yang et al, 2005;Lu et al, 2006;Jin et al, 2020), protease has been characterized as one of the potential drug targets among coronaviruses (Anand et al, 2003). In this sense, many recent studies suggested that the selection of various FDA-approved antiviral compounds may yield promising results against COVID-19 infection (Chang et al, 2016;Chang et al, 2020;Contini, 2020;Gonzalez-Paz et al, 2020;Khan et al, 2020;El ky, 2020a;Islam et al, 2020;Sinha et al, 2020;Wahedi et al, 2020;Kundu et al, 2020;Das et al, 2020;Abdelli et al, 2020 ). Chang et al, 2020 reported that chloroquine, an older antimalarial drug, has ability to inhibit the viral 3CLprotease activity.…”
Section: Introductionmentioning
confidence: 99%
“…Identified first time in Wuhan city of China in late December 2019 (Aanouz et al, 2020;Elfiky & Azzam, 2020;Elmezayen et al, 2020;Enayatkhani et al, 2020;Fausto et al, 2020;Ghosh et al, 2020;Muralidharan et al, 2020;Phulen et al, 2020;Rajib et al, 2020;Rothan & Byrareddy, 2020;Rowan & Laffey, 2020;Salman et al, 2020;Sourav et al, 2020;Umesh et al, 2020), Covid19 is a respiratory disease that is caused by the new coronavirus SARS-CoV-2 (Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-Cov-2) 2019 (Abdelli et al, 2020;Rakesh et al, 2020;Rameez et al, 2020;World Health Organization, 2020). Covid19 is the name given by the World Health Organization (WHO) on 11 February 2020 (World Health Organization, 2020).…”
Section: Introductionmentioning
confidence: 99%